Wake Forest College Magnolia Queen and Court, 1961. - (:unkn) unknown (Forsyth County Public Library)
WSJ 5-14-61 p.1C.
Wake Forest College Magnolia Queen and Court, 1961. The people are: Wanny Wagster, Queen Gladys Morgan, Jennifer Jones, and Bill Blackburn.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth